(untitled) (Journal of Accessibility and Design for All, 2023)
The introduction of WCAG 2.0 and the European Web Accessibility Directive marked significant milestones in the realm of web accessibility evaluation. However, even with the passage of considerable time, persistent challenges continue to impact the assessment of web accessibility. In this article, we aim to address these ongoing hurdles and provide comprehensive suggestions for accessibility assurance to achieve efficiency, consistency, and transparency in the processes of preparing accessibility statements, monitoring, and self-assessment. The proposed solutions include a centralised system for preparing accessibility statements, a centralised government template for feedback mechanisms, simplified self-assessment based on nine general criteria, and in-depth monitoring by experts and individuals with disabilities. Centralising all accessibility statements would facilitate monitoring updates and accessibility achievements, enabling mass verification by the bodies in charge of monitoring the Web Accessibility Directive and the public. The centralised government template for feedback mechanisms provides benefits such as automatic form completion and shared responsibility for addressing reported inaccessible content. Simplified, centralised, and automated monitoring allows for efficient tracking of accessibility status and verification of updates using an automated software environment. Links to results can be shared with public sector bodies and inspectors, enhancing transparency and comparison. In-depth monitoring requires complete analysis and recommendations for improvements, in which experts and individuals with disabilities are involved. Proper education and training of website administrators are crucial for ensuring quality and meeting accessibility criteria. By implementing these proposals, the goal of inclusive access to information and services can be achieved for all users.